Assessing the role of market integration in the consumption of traditional foods in Benin: a joint price instability coefficient and diet composition approach - Honfoga, B.G.; N’tandou-Bonzitou, G.; Vodouhe, R.S.; Bellon, M.R.; Hounhouigan, Joseph D. (Springer, 2018)
Globalization-driven food trade policies and the transformations of food regimes have led to modernizing food habits and the growing substitution of traditional foods by introduced/industrialized foods in the diets of urban people in sub-Saharan Africa. Such changes in food consumption habits are suspected to be associated with the increasing prevalence of some non-transmittable food-related diseases in the region. The role food markets play in food substitution in the diets needs to be understood. This study analyzes the effects of differential market integration on the consumption of the two types of foods in Southern Benin. Market integration was assessed using the reciprocal of the gap in price instability coefficients between markets (G) and calculated using monthly prices series over the “July 2009–July 2011” period. The findings indicate that markets in the Allada market cluster are more integrated for introduced foods (G = 5.3) than traditional foods (G = 4.3). The integration of primary, assembly, and rural consumer markets with the Bohicon regional market is by far higher for introduced foods (G = 5.3) than traditional foods (G = 1.2). The results in Toffo market cluster were comparable, in spite of less reliable data. The district-level rural markets are more integrated among themselves than with the regional market, either for traditional foods or introduced foods. Considering that most of the latter are processed foods, the result tends to indicate that food processing would trigger greater market integration. Therefore, policies that promote processing and trade of locally produced traditional foods should be implemented. Indeed, processing is key among the factors that increase urban consumers’ preferences for introduced foods against traditional foods. On the contrary, the hypothesis which asserts that low levels of market integration among traditional foods contribute to their disappearance in people’s diets is rejected. Indeed, diets in rural areas of Benin are still dominated by “traditional foods.” However, the growing trend in the consumption of imported low nutritional value foods should be controlled by appropriate food production and trade policies.